PERAN HEDONIC SHOPPING VALUE MEMEDIASI PENGARUH STORE ATMOSPHERE TERHADAP IMPULSE BUYING - Putra, Ida Bagus Dwi Sutiyasa; Warmika, I Gde Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study was to explain the role of the Hedonic Shopping Value in mediating the influence of the atmosphere store on impulse buying. This research was carried out in the city of Denpasar. Samples taken as many as 100 respondents through the purposive sampling method and were distributed using a Google Form questionnaire with customized criteria. The data analysis technique used is a classic assumption test, path analysis (path analysis) and a Sobel test. The results of this study indicate that all hypotheses are accepted. Store atmosphere has a positive and significant effect on impulse buying. The atmosphere store has a positive and significant effect on the Hedonic Shopping Value. Hedonic Shopping Value has a positive and significant effect on impulse buying. Hedonic Shopping Value plays a significant role in mediating the influence of atmospphere stores to impulse buying. The implications of this study are in increasing impulse buying, the Sun Department Store Duta Denpasar Duta is expected to provide a good atmospphere store to the visitors because with a good setting of atmosphere will stimulate positive emotional conditions so that it finally causes a pleasant shopping experience and causes hedonic Shopping Value Inside consumers.